The Representation of Character Education in the Movie Sang Prawira Based on Thomas Lickona’s Theory - Brilianti, Amalia Eka (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
The film is the favorite literary work teachers adopt to teach students character education. The Sang Prawira movie (2019) contains an educational character message and motivation to reach the dreams of society, especially the young generation. The study of character education representation based on Thomas Lickona's theory has yet to be investigated by previous studies. This study aims to investigate the character education representation based on Thomas Lickona's theory that is strongly represented in Sang Prawira's movie. This study uses the qualitative method using the theory of character education by Thomas Lickona. Based on the study, the researcher found the representation of character education, such as drug education as the moral principle, fortitude in fighting for kindness, positive attitude through hope and support, humility in admitting mistakes, wisdom through the ability to make decisions, loving to god almighty and all humans, hard work to achieve the dreams, the integrity recognition as ethical consistency, the gratitude by realizing obligation, justice in recognizing the responsibilities. In conclusion, the representation of the educational character in this film should be obtained by many Indonesian students because it becomes an example and guideline for them to implement good moral knowledge, behavior, and feeling in broader society.